2023
DOI: 10.3390/ijerph20043115
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Aesthetic Value of Waterfront Green Space Based on Space–Psychology–Behavior Dimension: A Case Study along Qiantang River (Hangzhou Section)

Abstract: As an important part of urban green infrastructure, the landscape effect of the urban waterfront green space varies, and sometimes, the green space with an excellent landscape aesthetic value fails to serve the needs of most citizens. This seriously affects the construction of a green ecological civilization and the implementation of the concept of “common prosperity” in China. Based on multi-source data, this study took the Qiantang River Basin as an example, selected 12 representative waterfront green spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…(2) Duration of stay The majority of findings suggested that visitors' duration of stay along urban river corridors is typically short, approximately one hour [70][71][72][73][74][75][76]. However, this study reveals diverse visitor stay duration.…”
Section: Social Attributes Influencing Recreational Experiences Of Ur...mentioning
confidence: 78%
“…(2) Duration of stay The majority of findings suggested that visitors' duration of stay along urban river corridors is typically short, approximately one hour [70][71][72][73][74][75][76]. However, this study reveals diverse visitor stay duration.…”
Section: Social Attributes Influencing Recreational Experiences Of Ur...mentioning
confidence: 78%
“…The majority of these studies consistently reported that walking is the predominant mode of transportation for individuals accessing urban river corridors (Gong et al, 2019;Ouyang & Wu,2023;Xie et al, 2023;Zhang et al, 2022;Zhao et al, 2021;Zhou et al, 2022). Other modes of transportation were found, including public transportation, private vehicles, sightseeing buses, and multi-bikes (Liu et al, 2023;Othman et al, 2021;Völker & Kistemann,2013;Zhang et al, 2022b). A study investigating the preferences and attitudes of citizens towards urban riversides revealed that individuals residing farther from the river corridors primarily relied on private vehicles, which may raise concerns regarding traffic connectivity and parking availability (Wang et al, 2020).…”
Section: Personal Attributesmentioning
confidence: 96%
“…An equal number of studies examine personal motivation as a variable (n=29, 49%). Individuals visit urban riversides primarily for physical exercise, recreation and leisure, including activities such as walking or jogging, cycling, swimming, dancing, skateboarding, rowing, dragon boat racing, water marathons, dog walking, picnicking, dining, photography, social gatherings, commuting, chess, and camping (e.g., Chen & Ma, 2023;Gargiulo et al, 2020;Guo et al, 2022;Gong et al, 2019;Liu et al, 2023;Meng et al 2020;Vierikko & Yli-Pelkonen, 2019;wade et al, 2023;Wu et al, 2019a;Yu et al, 2022;Zhang et al, 2022b;Zingraff-Hamed et al, 2022). Furthermore, two studies also discussed the motivation for restoration (Gargiulo et al, 2020;Jakstis et al, 2023).…”
Section: Personal Attributesmentioning
confidence: 99%
See 1 more Smart Citation